Sulfometuron methyl-sensitive and -resistant acetolactate synthases of the archaebacteria Methanococcus spp. - Xing, R Y (1987)
The herbicide sulfometuron methyl (SM) inhibited growth of some methanococci. Of 28 strains tested, the growth of 7 was completely inhibited by 0.55 mM SM. Growth of an additional 14 strains was partially inhibited, and the growth of 7 strains was unaffected by this concentration of SM. In some cases, the branched-chain amino acids protected growth. Growth inhibition was correlated with the Ki for SM of acetolactate synthase (ALS). For the enzymes from bacteria representative of the sensitive, partially resistant, and resistant methanococci (Methanococcus aeolicus, Methanococcus maripaludis, and Methanococcus voltae, respectively), the Ki for SM was 0.0012, 0.34, and greater than 1.0 mM, respectively. Inhibition was uncompetitive with respect to pyruvate. Based on these observations, ALS appeared to be the major if not the sole site of action of SM in the methanococci. The sensitivity of the ALS from these three methanococci to feedback inhibition by branched-chain amino acids was also quite different. Although all three were sensitive to feedback inhibition by valine, the Ki varied 20-fold, from 0.01 to 0.22 mM. Moreover, only the ALS from M. maripaludis was sensitive to inhibition by leucine, and the Ki was 1.8 mM. The Ki for isoleucine for the ALS from both M. maripaludis and M. voltae was about 0.1 mM. The ALS from M. aeolicus was not inhibited by isoleucine. In other respects, the ALSs from the methanococci were very similar. After dialysis, thiamine pyrophosphate but not FAD and Mg2+ was required for maximal activity, and they were all rapidly inactivated by oxygen. Although the methanococcal ALSs exhibited diverse properties, the range of catalytic and regulatory properties closely resembled those of the eubacterial enzymes.